2018
DOI: 10.1186/s40981-017-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflationary non-invasive blood pressure (iNIBP) monitoring technology and conventional deflationary non-invasive blood pressure (dNIBP) measurement in detecting hypotension during cesarean section

Abstract: BackgroundThe Nihon Kohden linear inflationary non-invasive blood pressure (iNIBP) monitoring technology is an oscillometric device that measures blood pressure by detecting oscillations during inflation. Systolic blood pressure can be recorded without overinflating the cuff higher than the true systolic pressure. Thus, total time taken for inflation and deflation is shorter than that by the conventional deflation devices. In this study, the ability of iNIBP to detect maternal hypotension during cesarean secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…Nukita et al (2020) reported that the repeated estimation of BP on the inflation phase can significantly reduce the risk of subcutaneous hemorrhage. Yamashita and Irikoma (2018) conclude that NIBP detection on cuff inflation detected hypotension faster than conventional NIBP without compromising the reliability of measurement, thus leading to early treatment of maternal hypotension and the prevention of adverse events related to the mother and the fetus. The efficacy of a new BP monitor (Takahashi et al 2020), based on detection of BP during inflation was evaluated in a randomised controlled study.…”
Section: Discussionmentioning
confidence: 86%
“…Nukita et al (2020) reported that the repeated estimation of BP on the inflation phase can significantly reduce the risk of subcutaneous hemorrhage. Yamashita and Irikoma (2018) conclude that NIBP detection on cuff inflation detected hypotension faster than conventional NIBP without compromising the reliability of measurement, thus leading to early treatment of maternal hypotension and the prevention of adverse events related to the mother and the fetus. The efficacy of a new BP monitor (Takahashi et al 2020), based on detection of BP during inflation was evaluated in a randomised controlled study.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the apparent advantages regarding maternal safety, the effects on the foetus remain controversial. As a result of an acute reduction in uteroplacental blood flow, spinal anaesthesia (SA) may lead to foetal acidosis, hypoxia or low Apgar scores (2,3). Evidence that the effects of drugs in GA affect neonatal neurological consequences (7) continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] However, in order to reduce the time of measurement and pressure required, some automatic oscillometric devices measure BPs during cuff inflation. 7,8 Some researchers quantified the influence of different cuff deflation and inflation rates on BP measurement. King compared the auscultatory BPs measured by two deflation rates of 2.35 and 4.7 mmHg per second, and found a significant effect.…”
Section: Introductionmentioning
confidence: 99%